Evaluating the acute effect of compression socks for recovery between exercise bouts - Leabeater, A.; Clarke, A.; James, L.; Huynh, M.; Driller, M. (Journal of Human Sport & Exercise, 2023)
The current study aimed to investigate the acute application of compression socks for recovery after a strenuous bout of lower-body exercise. 58 active young adults (29 females, 29 males) performed ankle range of motion, calf circumference, isometric strength, calf endurance and perceived muscle soreness measures at baseline, and up to 48 hours following a strenuous bout of lower-body exercise. During the 30-minute recovery period, participants were randomly assigned an experimental leg (compression sock - COMP) and a control leg (passive recovery - CON). No significant group x time interactions were recorded (p > .05) and effect sizes were mostly trivial, except for a small decrease in perceived muscle soreness in COMP compared to CON immediately post-recovery (d = -0.29). For both groups, calf circumference increased, and calf endurance was reduced following exercise (p < .001), while perceived muscle soreness increased significantly over the follow-up period compared to baseline (p < .001). The application of compression socks for 30-minutes following intense calf exercise had little effect on physical measures but may result in a small decrease in perceived muscle soreness immediately following their use for recovery. These garments could be a viable recovery option for athletes with a short timeframe in between training bouts.